2020
DOI: 10.3892/ol.2020.11249
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‑210 is a potentially non‑invasive biomarker for the diagnosis and prognosis of glioma

Abstract: MicroRNAs (miRs) transferred by exosomes can function as non-invasive potential biomarkers for the diagnosis and prognosis in various types of cancer. The present study examined the diagnostic and prognostic value of serum exosomal-(exo-)miR-210 levels in association with hypoxic conditions in patients with glioma. Serum levels of exo-miR-210 were determined by quantitative PCR in samples obtained from patients with glioma. Patients were divided into low-and high-expression exo-miR-210 groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…It has been reported that exosomal microRNA-21 could be considered as a potential biomarker for the early diagnosis of pancreatic cancer using a tethered cationic lipoplex nanoparticle biochip (38). Furthermore, exosomal microRNA-210 is a potentially non-invasive biomarker for the diagnosis and prognosis of glioma (39). In breast cancer, >30 miRNAs have been confirmed to be associated with breast cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that exosomal microRNA-21 could be considered as a potential biomarker for the early diagnosis of pancreatic cancer using a tethered cationic lipoplex nanoparticle biochip (38). Furthermore, exosomal microRNA-210 is a potentially non-invasive biomarker for the diagnosis and prognosis of glioma (39). In breast cancer, >30 miRNAs have been confirmed to be associated with breast cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…21 Many scientists try to find effective biomarkers such as tumor-related genes, microRNAs and long noncoding RNAs. [22][23][24] Compared with other biomarkers, 25 lncRNAs are considered to be ideal biomarkers because of their important regulation effect in glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the functional and mechanical roles of miRNAs in different types of human cancer (18,48,52). In CRC, several miRNAs have been identified to be critical molecular regulators interplaying with important molecular pathways, and thus play key roles in the initiation and progression of CRC (24,54,56).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have performed differential expression analyses of miRNAs in several types of cancer to investigate the role of miRNAs as clinical biomarkers and identified some miRNAs whose aberrant expression levels are associated with pathological and clinical phenotypes of patients with cancer ( 44 – 46 ). Increased miR-210 expression has been reported in several types of cancer, including non-small cell lung cancer ( 47 ), glioma ( 48 ), CRC ( 49 ) and higher expression of miR-210 correlated with worse recurrence free survival or disease free survival (RFS/DFS), overall survival (OS), metastasis free survival or distant relapse free survival (MFS/DRFS) in breast cancer. For RFS/DFS, OS and MFS/DRFS, the combined hazard ratio (HR) and 95% confidence interval (95% CI) of higher miR-210 expression were 3.36 (2.30, 4.93), 3.29 (1.65, 6.58) and 2.85 (1.76, 4.62) in patients with breast cancer, respectively ( 50 ).…”
Section: Discussionmentioning
confidence: 99%